Monte Carlo study of a generalized icosahedral model on the simple cubic lattice - Hasenbusch, Martin (Physical review, 2020)
We study the critical behavior of a generalized icosahedral model on the simple cubic lattice. The field variable of the icosahedral model might take 1 of 12 vectors of unit length which are given by the normalized vertices of the icosahedron as value. Similar to the Blume-Capel model, where in addition to -1 and 1, as in the Ising model, the spin might take the value 0, we add in the generalized model (0,0,0) as allowed value. There is a parameter D that controls the density of these voids. For a certain range of D, the model undergoes a second-order phase transition. On the critical line, O(3) symmetry emerges. Furthermore, we demonstrate that within this range, similar to the Blume-Capel model on the simple cubic lattice, there is a value of D, where leading corrections to scaling vanish. We perform Monte Carlo simulations for lattices of a linear size up to L = 400 by using a hybrid of local Metropolis and cluster updates. The motivation to study this particular model is mainly of technical nature. Less memory and CPU time are needed than for a model with O(3) symmetry at the microscopic level. As the result of a finite-size scaling analysis we obtain nu = 0.711 64(10), eta = 0.037 84(5), and omega = 0.759( 2) for the critical exponents of the three-dimensional Heisenberg universality class. The estimate of the irrelevant renormalization group eigenvalue that is related with the breaking the O(3) symmetry is y(ico) = -2.19(2).
Gesehen am 23.07.2020